Multi-walled carbon nanotubes growth by chemical vapour deposition: Effect of precursor flowing path and catalyst size. (January 2022) - Chan, K.F.; Maznam, N.A.M.; Hazan, M.A.; Ahmad, R.N.A.; Sa'ari, A.S.; Azman, N.F.I.; Mamat, M.S.; Rahman, M.A.A.; Tanemura, M.; Yaakob, Y.
Abstract: Carbon nanomaterials have been found to have promising performance in various applications. However, the complexity and high operation cost during the fabrication still limit the mass production. In this study, multi-walled carbon nanotubes (MWCNTs) were grown on nickel oxide (NiO) via chemical vapour deposition (CVD) with ethanol as the carbon precursor. The NiO catalyst was fabricated from a nickel nitrate – ethanol mixture. The particle size of NiO was altered through high-energy ball milling for 0, 4, and 7 h. The influence of precursor flowing path (D) and NiO catalyst size during the MWCNTs growth have been investigated. The Raman spectra showed that the crystallite size of MWCNTs (La ) increased from 16.97 to 18.00 nm as the NiO milling time increased. Furthermore, NiO-catalysed MWCNTs at D = 12 cm achieved the highest carbon yield (80.54%), with an ID /IG ratio of 1.134. Also, SEM and TEM revealed that the larger size of NiO catalyst produced fewer layers of MWCNTs. These findings are significant to aid researchers and manufacturers in optimising the CVD process towards large-scale MWCNTs fabrication.